Adherence to 24-Hour Movement Guidelines among Spanish Adolescents: Differences between Boys and Girls - Miguel Angel Tapia-Serrano; Javier Sevil-Serrano; Pedro Antonio Sánchez-Miguel (Children, 2021)
Background: The 24-Hour Movement Guidelines for adolescents recommend ≥60 min/day of moderate-to-vigorous physical activity (PA), ≤ 2 h/day of screen time, and 8–10 h/day of sleep. Since little information is available on the 24-Hour Movement Guidelines in Spanish adolescents, this study aims to estimate the proportion of Spanish adolescents meeting individual and combinations of these 24-Hour Movement Guidelines. Moreover, another aim of this study is to examine gender differences in compliance with 24-Hour Movement Guidelines. Methods: A final sample of 1465 Spanish adolescents (44.50% girls; 13.08 ± 0.86) participated in this cross-sectional study. The 24-Hour Movement Guidelines were measured during weekdays and the weekend days by self-reported questionnaires. Results: Although most adolescents met sleep duration guidelines (81.3%), only 38% and 15.8% met physical activity and screen time guidelines, respectively. Only 5.4% of these adolescents met all three 24-Hour Movement Guidelines, whereas 10.2% of this sample did not meet any of these guidelines. Although boys reported greater compliance with physical activity recommendations and girls with screen time recommendations, no significant gender differences were found in the compliance of all three 24-Hour Movement Guidelines. Conclusion: Given that 94.4% of Spanish adolescents did not meet 24-Hour Movement Guidelines, promoting all these three movement behaviours in both boys and girls is an urgent public health priority.